ANALISIS RASIO CAMEL PADA PT. BANK PEMBIAYAAN RAKYAT SYARIAH RAHMAH HIJRAH AGUNG KOTA LHOKSEUMAWE DAN PT. BANK PERKREDITAN RAKYAT SABEE MEUSAMPE KABUPATEN ACEH UTARA TAHUN 2015-2016 - STIE Lhokseumawe (JAKTABANGUN: Jurnal Akuntansi dan Pembangunan, 2017)
The purpose of this study is to determine the soundness of banks in PT. BankPembiayaan Rakyat Syariah (BPRS) Rahmah Hijrah Agung Kota Lhokseumawe andPT. Bank Perkreditan Rakyat (BPR) Sabee meusampe using CAMEL ratio from 2015to 2016, and to know how predicate bank performance in PT. Bank PembiayaanRakyat Syariah (BPRS) Rahmah Hijrah Agung Kota Lhokseumawe and PT. BankPerkreditan Rakyat (BPR) Sabee Meusampe Kabupaten Aceh Utara Court from 2015until 2016. the authors are interested in conducting research with the title “RatioAnalysis CAMEL In the Bank Pembiayaan Rakyat Syariah (BPRS) Rahmah HijrahAgung Kota Lhokseumawe and PT. Bank Perkreditan Rakyat (BPR) Sabee MeusampeKabupaten Aceh Utara “. In this research method used is quantitative method suchas the numbers of the Balance Sheet, Profit / Loss Report, Report of Assets Quality,and Capital Adequacy Reports. Qualitative research with descriptive approach tomeasure the financial performance of banks to perform calculations using financialratios CAMEL (Capital, Assets, Managemet Earnings, and Liquidity). The results ofthe assessment results of BPRS Rahmah Hijrah Agung and PT. Bank PerkreditanRakyat (BPR) Sabee Meusampe Kabupaten Aceh Utara Great move by using theCAMEL from 2015 to 2016 received the title FAIR . Suggestions in this research isto improve the quality of productive assets is a good idea if the BPRS RHA and BPRSabee Meusampe maintain or increase the number of PPAP formed so as to coverrisks that may arise if the velocity of earning assets less current and in line withefforts to reduce the number of troubled loans, particularly those categorized badcredit.